Pelatihan Pembuatan Kompos dari Seresah Daun dan Sampah Organik untuk Ibu-ibu PKK Dusun Tretes dan Kelompok Tani Hutan Pujon Hill - Wibowo, Febri Arif Cahyo; Fitri, Ayu Chandra Kartika; Boedirochminarni, Arfida; Prakosa, Galit Gatut; Aditya, Sukma Arty Purwa; Nurmalasari, Desi; Handayani, Novita Safitri; Alhaqie, Iqbal Arif; Dinata, Muhammad Agung (Universitas Tribhuwana Tunggadewi Malang, 2024)
The village development program is an initiative aimed at improving the welfare of rural communities through various training and empowerment activities carried out by UMM and UNITRI Malang lecturers with target partners, the Pujon Hill Forest Farmer Group (KTH) and the PKK mothers of Tretes Hamlet along with the Government/Local Government. Bendosari Village is one of the villages located in the mountains and highlands of Pujon District. Almost all of the community's land is used for agriculture and plantations. There are several spots of waste accumulation at the service location, ranging from livestock waste to household organic waste, which is a significant problem that needs to be addressed because there is no location for waste disposal. Thus, composting technology is required for leaf litter, household waste, and livestock waste. The stages of the Community Service activity method are: a). Establishment of KTH and PKK mothers' institutions, b). Training in processing household, agricultural, livestock, and forest leaf litter waste into organic compost, then analyzing its quality with laboratory tests; c). application of leaf waste shredding machine technology, plastic drums/composters, and demonstration plots for compost storage; d). Packaging technology training and compost product packaging design, e). Introduction and planting of essential plants that play a role in inhibiting soil erosion and have the potential to become essential oils, such as citronella. The results that have been achieved include organic compost products that can be marketed under the Ekombi brand, activity posters, activity videos, Partner Institutional Decrees, ISBN books, HKI Waste shredder tools, and participation in National seminars. This program has succeeded in providing a positive impact, especially in increasing public awareness of the importance of waste processing and sustainable forest land management.ABSTRAKProgram bina desa merupakan salah satu inisiatif yang bertujuan untuk meningkatkan kesejahteraan masyarakat di daerah pedesaan melalui berbagai kegiatan pelatihan, dan pemberdayaan yang dilakukan oleh dosen UMM dan UNITRI Malang dengan mitra sasaran Kelompok Tani Hutan Pujon Hill (KTH) dan Ibu-ibu PKK Dusun Tretes beserta Pemerintah/Pemda. Desa Bendosari merupakan salah satu desa yang berada di pegunungan dan dataran tinggi kecamatan pujon. Hampir seluruh lahan masyarakat yang ada digunakan untuk pertanian dan perkebunan. Terdapat beberapa spot penumpukan sampah di lokasi pengabdian, mulai dari kotoran ternak, dan limbah organik rumah tangga menjadi permasalahan penting yang perlu diatasi karena belum ada lokasi untuk pembuangan sampah. Sehingga, diperlukan adanya teknologi pembuatan kompos dari serasah daun, limbah rumah tangga, dan kotoran ternak. Tahapan metode kegiatan Pengabdian yaitu: a). Pembentukan kelembagaan KTH dan Ibu-Ibu PKK, b). Pelatihan pengolahan limbah rumah tangga, pertanian, peternakan dan serasah daun hutan menjadi kompos organik, lalu menganalisa kualitasnya dengan uji laboratorium, c). penerapan teknologi mesin pencacah sampah daun dan drum plastic/komposter serta demplot untuk tempat penyimpanan kompos, d). Pelatihan teknologi pengemasan dan desain pengemasan produk kompos, e). Pengenalan dan penanaman tanaman atsiri yang berperan dalam menahan laju erosi tanah dan berpotensi menjadi minyak atsiri, seperti serai wangi. Hasil yang sudah dicapai, antara lain produk kompos organik yang bisa dipasarkan dengan merk ekombi, poster kegiatan, video kegiatan, SK Kelembagaan Mitra, buku ber-ISBN, HKI Alat pencacah limbah, dan keikutsertaan dalam seminar Nasional. Program ini berhasil memberikan dampak positif, terutama dalam meningkatkan kesadaran masyarakat tentang pentingnya pengolahan sampah dan pengelolaan lahan hutan yang berkelanjutan.